Sense of (non)belonging – international student life in times of crisis : A case study of international degree students in Finnish university - Tarkio, Fanny-Sofia (My University, 2022)
The purpose of this study is to examine the experiences of the first year international Master´s degree students in Finland during a global pandemic COVID-19. Since 2020, the outbreak has affected the rhythms of life and therefore, the international student´s opportunities to socialize and be mobile have changed. The study draws attention on the question how physical isolation in the early state of studies effects the feelings of belonging. This research is part of international students in times of crisis: EqualISM research project that has been launched in 2020. Eight semi-structured interviews were conducted during the spring and summer 2021. The qualitative data was analyzed with content analysis. The phenomenon of sense of belonging is inspected through concepts of place, space and mobility which combined, allows to see past the general conception of students´ sense of belonging as mainly academic engagement. The findings indicate that international students develop sense of belonging through ways in which they engage with local practices and opportunities in the course of their everyday life. The students´ mobilities were prompted by longing to be part of something. To cultivate attachment, the context or the place had to be experienced together with others, although socialization itself did not guarantee the development of sense of belonging. The emergence of emotional bond between the students and the social or physical context, was due to interpretation of experiences through the lens of relatedness (kinship) and mattering and care (presence). To conclude, the pandemic limited students´ access to places and opportunities to be mobile, which in turn affected their cultivation of sense of belonging. The higher education institutes should acknowledge the importance of mobility as a tool for cultivating sense of belonging. Additionally, more attention needs to be given for spaces that engenders sense of belonging during remote learning if the current situation continues or repeats itself driving people back to social distancing.
Keywords: International students, higher education COVID-19, sense of belonging, space, place, mobility